2019
DOI: 10.1002/adom.201901389
|View full text |Cite
|
Sign up to set email alerts
|

All‐Dielectric Kissing‐Dimer Metagratings for Asymmetric High Diffraction

Abstract: and vortex beam generators. [10][11][12] In particular, phase-gradient metasurfaces can cumulatively produce blazed phase profiles for essential far-field interference to redirect the incident wave to the anticipated direction under normal incidences. [13][14][15] However, these approaches suffer from the intrinsic restriction owing to the limited number of elements in a supercell which can fit into each periodically repeated units to discretely map the desired phase profiles. Apparently, phase-gradient metasu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Metasurfaces, which consist of periodic arrays of carefully designed nanostructures, provide a versatile platform to accurately control the properties of light, including phase, amplitude, polarization and frequency spectrum of light [1]. In recent years, metasurfaces based on dielectric materials with high refractive index have been used to develop numerous compact optical devices due to their low loss properties, including at lenses [2][3][4], beam de ectors [5,6], holograms [7,8], etc. Searching for the ultrahigh Q-factor resonant structures with strong mode coupling has attracted much attention recently [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Metasurfaces, which consist of periodic arrays of carefully designed nanostructures, provide a versatile platform to accurately control the properties of light, including phase, amplitude, polarization and frequency spectrum of light [1]. In recent years, metasurfaces based on dielectric materials with high refractive index have been used to develop numerous compact optical devices due to their low loss properties, including at lenses [2][3][4], beam de ectors [5,6], holograms [7,8], etc. Searching for the ultrahigh Q-factor resonant structures with strong mode coupling has attracted much attention recently [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–4 ] By introducing strong interactions between electromagnetic (EM) waves and meta atoms, metasurfaces have shown great potentials in full vectorial EM manipulation in terms of amplitude, phase, as well as polarizations. So far, many exotic applications such as perfect absorption, [ 5,6 ] anomalous beam deflection, [ 7,8 ] vortex beam generation, [ 9 ] flat lensing, [ 10,11 ] and meta‐hologram [ 12 ] have been realized with simultaneous high performance and compactness compared with their traditional counterparts. Besides, metasurface‐based devices can even achieve counterintuitive functionalities that can hardly be realized by natural materials, such as carpet cloaking [ 13 ] and daytime radiative cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the unique capability to create unidirectional light radiation in multiple architectures, including single-element nanospheres [ 8 , 9 ], nanodisks [ 11 , 12 , 13 , 14 , 15 ], nanowires (cylinders) [ 16 , 17 , 18 , 19 ], rectangular patches [ 20 ], V-shaped [ 21 ] and stair-shaped nanoantennas [ 22 ], as well as multi-element array nanoantennas [ 23 , 24 , 25 , 26 ]. There are also many efforts in the field to achieve bi- or multi-directional scattering/emission [ 9 , 13 , 15 , 21 , 23 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%